What Is the Best Regimen for Ovarian Stimulation of Poor Responders in ART/IVF? - Blumenfeld, Zeev (Frontiers in Endocrinology, 2020)
The infertile patients with aging ovaries, also sometimes referred to as impending premature ovarian insufficiency (POI), or impending premature ovarian failure (POF), or poor ovarian responders (POR), constitute a significant and increasing bulk of the patients appealing to IVF/ART. Different causes have been cited in the literature, among the identified etiologies, including chromosomal and genetic etiology, metabolic, enzymatic, iatrogenic, toxic, autoimmune and infectious causes. Although the most successful and ultimate treatment of POI/POF/POR patients, is egg donation (ED), many, if not most, of these infertile women are reluctant to consent to ED upon the initial diagnostic inter¬view, requesting alternative solutions despite the low odds for success. Despite anecdotal case reports, no unequivocal treatment proved to be successful, for these patients, in prospective randomized controlled trials. Nevertheless, the addition of growth hormone (GH) to ovarian stimulation in POR with GH deficiency, may improve the results of COH and the IVF success. In patients with autoimmune etiology to POR/POI the combination of glucocorticosteroids, pituitary-ovarian suppression, and COH may be successful in achieving the desired conception.